Respectus Philologicus, 2009 Nr. 16 (21) A - Bankauskaitė, Gabija (Respectus Philologicus, 2009)
CONTENTSI. DISCOURSE: THE RESEARCH PROBLEMS OF GENERATION, PERCEPTION AND IMPACTAgnieszka Miksza (Poland). The Politics of Reading and Writing. Jeanette Winterson’s Dialogue with Herself and the Reader... 11Olga Glebova (Poland). Recontextualisation as an Interpretive Strategy in Contemporary Novelistic Discourse ... 19Wojciech Majka (Poland).Understanding as Context for Disclosure ... 30Jurgita Vaičenonienė (Lithuania). Cultural Translation and Linguistic Metaphor: A Case Study of Verbal Metaphor Translation ... 38Regina Koženiauskienė (Lithuania). The Manipulation of Headlines: The Opposition of Text and Context... 50Erika Rimkutė, Neringa Pakalnytė (Lithuania). Topics and Linguistic Features of Social Advertisements...57Dovilė Vengalienė (Lithuania). The Cultural Aspects of Auto-Ironic Blends Referring to Lithuania and America in News Headlines ... 73Solveiga Sušinskienė (Lithuania). Nominalization as a Micro-Structural Item of English Scientific Discourse ...84II. LITERARY FICTION: INTERPRETATION POSSIBILITIESUgnius Keturakis (Lithuania). Two Ways Leading to Modern National Culture: Vincas Kudirka and Jurgis Baltrušaitis... 93Marek Smoluk (Poland). The English Royal Court through the Eyes of Erasmus ... 105Ingrida Žindžiuvienė (Lithuania). Location and Space in Don Delillo’s Cosmopolis and Antanas Škėma’s Balta drobulė ... 112III. CONTEMPORARY RESEARCH INTO LITHUANIAN LINGUISTICS: LINGUISTIC AND EXTRALINGUISTIC APPROACHESJonas Andrijauskas, Lina Bačiūnaitė-Lužinienė, Vytas Kriščiūnas (Lithuania). The Employment of New Technologies in Diachronic Toponymy ... 123Saulė Juzelėnienė, Giedrė Baranauskaitė (Lithuania). The Expression of Semantic Group of Movement in the Air in the Lithuanian and English Languages... 135Robertas Kudirka (Lithuania). The Formant Structure of the Accented Long and Short Vowels in the Lithuanian Standard Language... 141Jurga Kerevičienė (Lithuania). Dativus iudicantis in Lithuanian and its Equivalents in English ... 153Daiva Aliūkaitė (Lithuania). Accuracy of Standard Language Images: the Problem of Quasistandard... 160Nijolė Tuomienė (Lithuania). Declension of the ā- and iā Stem nouns in the Peripheral Ramaškonys Subdialect... 188Rima Bacevičiūtė (Lithuania). Tendencies and problems of instrumental analysis of sounds in lithuanian dialectology... 202IV. SCIENTIFIC LIFE CHRONICLEBirutė Briaukienė (Lithuania). 110 Years to “Lietuviška gramatikėlė”...216Daiva Aliūkaitė, Gabija Bankauskaitė-Sereikienė (Lithuania). Young Linguists of the Lithuanian Language Gathering — a Part of Jubilee Events at VU KHF ...221V. REQUIREMENTS FOR PUBLICATION... 226VI. OUR AUTHORS... 234
Keywords: none